Strategi Inovasi Produk UMKM Dalam Menghadapi Globalisasi Melalui Digitalisasi - Fitriyani, Ika; Mustofa, Amirul; Yunus, Eddy (SENTRI: Jurnal Riset Ilmiah, 2025)
This study aims to explore how micro, small, and medium-sized enterprises (MSMEs) implement adaptive strategies that lead to global readiness in the digital economy era. Using a qualitative approach with a case study method, data were obtained through in-depth interviews with eight MSME actors. The findings reveal that the strategy of glocalization helps expand global market reach through digitalization, product innovation, the use of globally oriented social media, digital partnerships across regions, and the exploration of international market access. The research highlights that both digitalization and product innovation play crucial and complementary roles in enabling MSMEs in Sumbawa Regency to penetrate export markets amid increasingly competitive global economic challenges. Digital transformation facilitates easier access to market information, opens broader distribution networks, and enhances efficiency in marketing processes and communication with consumers. This study demonstrates that the courage and resilience of MSMEs have shown significant potential for integration into the global trade ecosystem. It underscores the importance of adapting to and leveraging digital technologies in modern business practices. Conceptually, this research contributes to a deeper understanding of locally based global strategies among small business actors. It emphasizes the need for continued mentoring, training, and the provision of technological infrastructure to achieve sustainable growth in the digital era.